Explaining child maltreatment: From behavior analysis to behavioral biology - BURGESS, ROBERT L.; DRAIS, ALICIA A. (Mexican Journal of Behavior Analysis, 2011)
<!--[if gte mso 9]> Normal 0 21 false false false ES-MX X-NONE X-NONE <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <mce:style><! /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Tabla normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-qformat:yes; mso-style-parent:""; mso-padding-alt:0cm 5.4pt 0cm 5.4pt; mso-para-margin-top:0cm; mso-para-margin-right:0cm; mso-para-margin-bottom:10.0pt; mso-para-margin-left:0cm; line-height:115%; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri","sans-serif"; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-fareast-font-family:"Times New Roman"; mso-fareast-theme-font:minor-fareast; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin;} --> <!--[endif]--> This paper begins with a brief overview of the history of research on the causes of child maltreatment and why the "social interactional" approach was developed by the first author (Burgess, 1979). This approach, based on fundamental principles of the experimental analysis of behavior, established the importance of interpersonal contingencies of reinforcement and punishment as proximate determinants of child abuse and neglect. Because of difficulties faced in successfully intervening with maltreating families and because of the importance of contextual factors operating at different levels of analysis, the authors examine "life-history theory", which is a centerpiece of behavioral biology, in an attempt to explain how personal, social and ecological factors, and interpersonal contingencies of reinforcement and punishment, combine to produce the family dynamics culminating in the abuse and neglect of children.